CSX in Practice: Tales of Challenge, Tales of Success - Anderson, Lauren; Wulfes, Jennifer; Rahimov, Aliagha; Huseynov, Afer; Mammadli, Farahim; Islam, Shariful; Krafft, Lea-Carlotta (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2023)
This chapter is structured into two sub chapters, studied and written by two research-groups, titled: (1) Tales of Challenge (2) Tales of Success. The chapter concludes with a common summary of all findings. In both sub chapters the same approach was applied. Semi-structured interviews were conducted and analyzed according to Mayring (2000) to collect perspectives from practice and research. Some interviews were conducted by each research group separately and some together. Also, a method inspired by Photovoice was used to gain a deeper understanding of specific challenges and drivers in the respective projects. Inspired by the Photovoice method (Wang and Burris, 1997), interviewees were asked to share a picture and short description answering a question posed by the researchers to gain a deeper understanding of specific challenges and drivers in the respective projects. Our shared main character, Joice, will keep popping up during this chapter to share her experience.